Climate Change and the Global Expansion of Dengue Fever: Epidemiological Trends and Public Health Challenges - Budiman (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2022)
Climate change has significantly influenced the transmission dynamics of dengue fever, particularly through rising temperatures, increased precipitation variability, and higher humidity levels. This study systematically examines the relationship between climate variability and dengue epidemiology, highlighting the expansion of Aedes aegypti vectors into previously non-endemic regions. A systematic literature review was conducted using PubMed, Scopus, and Google Scholar to analyze peer-reviewed studies published in the past decade. Key findings indicate that higher temperatures accelerate mosquito development and viral replication, leading to a shorter extrinsic incubation period. Additionally, fluctuating rainfall patterns create optimal breeding conditions, increasing the density of mosquito populations and dengue incidence rates. The results underscore the necessity for climate-adaptive public health policies, improved urban planning, and proactive vector control measures to curb disease transmission. Climate-based early warning systems, environmental management strategies, and interdisciplinary research integrating climatology and epidemiology are critical in mitigating future outbreaks. Given the escalating global burden of dengue fever, urgent and sustained efforts are required to address the challenges posed by climate change and safeguard vulnerable populations against increasing health risks.